Kala Manjari: 50 years of Indian classical music and dance in Singapore - RAMASWAMI, Seshan (Institutional Knowledge at Singapore Management University, 2015)
The development and spectacular growth of the Indian arts in Singapore over the last fifty years have mirrored the economic growth and development of the nation-state itself. This book takes readers through the fascinating history of Indian classical music and dance in Singapore. Memories of pioneering, established and rising artistes and arts administrators are woven into a vivid story of the evolution of these forms into their current vibrant state. The developmetn of North and South Indian genres of classical music, as well as of different styles of classical dance are described to give the reader a comprehensive hisotry of the major Indian performing art forms. The complementary roles of the temples, and of various enablers such as the Government and media are also described. Well-researched, with over a hundred personal interviews in Singapore and India, and lavishly illustrated with over 180 choice photographs, the book is a must-read for everyone who cares about the state of the Indian arts in Singapore.